Differences in growth responses between Cryptomeria japonica and Chamaecyparis obtusa planted in group selection openings in Kyushu, southern Japan. Issue 2 (4th March 2017) - Ito, Kazuki; Ota, Tetsuji; Mizoue, Nobuya; Yoshida, Shigejiro; Sakuta, Kotaro; Inoue, Akio; Ito, Satoshi; Okada, Hiroyuki
ABSTRACT: We quantified the differences in growth responses between Cryptomeria japonica and Chamaecyparis obtusa trees in approximately 0.1-ha group selection openings in southern Japan. We measured the position, height ( H ), and diameter at ground level ( D ) of 6- and 13-year-old C. japonica and C. obtusa trees that were planted in two respective openings. The annual H and D growth of C. japonica increased until trees were 10 and 8 m, respectively, distant from the nearest edge of the opening. For C. obtusa, the annual H and D growth increased slightly until the trees were 6 m distant from the nearest edge, but they did not significantly differ between 6 and 18 m distant from the nearest edge. While the shortest distance from the edge explained 63% and 50% of the variationsal H and D growth, respectively, of C. obtusa . Our result demonstrates that C. obtusa is less sensitive to edge effects than C. japonica . We conclude that C. obtusa is likely to be more suitable than C. japonica for planting within 0.1-ha group openings, as it will result in faster early stage growth, with less variation, within the openings.